Synopsis, 2013 annual trends and outlook report: Tracking key CAADP indicators and implementation - Bahiigwa, Godfrey; Collins, Julia; Makombe, Tsitsi; Jemaneh, Samson; Tefera, Wondwosen (International Food Policy Research Institute, 2015)
This Issue Note presents the current status and trends captured by key Comprehensive Africa Agriculture Development Programme (CAADP) indicators that ReSAKSS has been tracking since 2008, at continental and regional levels. ReSAKSS was established by the CAADP Partnership Platform, and later endorsed by the African Union Conference of agricultural ministers, to serve as the formal CAADP review and learning platform, charged with tracking 30 core CAADP indicators. The data for the current indicators are published in the ReSAKSS Annual Trends and Outlook Reports (ATORs) and on the ReSAKSS website (www.resakss.org), where they can be accessed in the form of maps and graphs and can be freely downloaded in excel format and used for analysis.